Does the Experience of International Mobility Lead to Career Advantages? Study of Russian researchers - G. L. Volkova (Высшее образование в России)
The current agenda of Russian scientific policy pays much attention to measures aimed at supporting the mobility of scientific personnel (including young ones). The purpose of this study is to analyze how the experience of international mobility affects the objective and subjective indicators of employment of Russian Doctorate Holders, and to find out whether the experience of working or studying abroad always gives advantages when returning to the home country. The empirical base of the study is the data of the project “Monitoring survey of Highly Qualified R&D Personnel” (N=1742 for the year 2019). The obtained results show that the impact of the international mobility on the careers of Russian researchers is a complex phenomenon that is not limited to positive effects. A number of advantages can be received for the “non-mobile career”, when loyalty to the current organization is rewarded. Along with the implementation of mobility support programs, it is necessary to create an institutional environment in which researchers with experience in international mobility can maximize their professional potential and have a favorable environment for building a scientific career.